Thymoma Patients Treated in a Phase I Clinic at MD Anderson Cancer Center: Responses to mTOR Inhibitors and Molecular Analyses - Wheler, Jennifer (Impact Journals LLC, 2013)
BACKGROUND: Thymomas and thymic carcinoma are rare tumors with no approved therapies. Our purpose was to analyze the molecular features and outcomes of patients referred to the Clinical Center for Targeted Therapy (Phase I Clinic). METHODS: We retrospectively reviewed the medical records of consecutive referred patients with advanced/metastatic thymoma or thymic carcinoma RESULTS: Twenty-one patients were identified (median age 52 years; 10 women; median number of prior systemic therapies = 2). Six of 10 patients (60%) treated with mTOR inhibitor combination regimens achieved stable disease (SD) ≥12 months or a partial response (PR). For patients treated on mTOR inhibitor regimens (N = 10), median time to treatment failure (TTF) was 11.6 months versus 2.3 months on last conventional regimen prior to referral (p=0.024). Molecular analyses (performed by next generation sequencing in seven patients and single polymerase chain reaction (PCR)-based assays in an additional six patients) showed diverse actionable mutations: PIK3CA (1 of 12 tested; 8%); EGFR (1 of 13; 8%); RET (1 of 7; 14%); and AKT1 (1 of 7; 14%). Of two patients with PIK3CA or AKT1 mutations, one was treated with an mTOR inhibitor-based regimen and achieved 26% regression with a TTF of 17 months. CONCLUSION: Patients with advanced/metastatic thymoma or thymic carcinoma demonstrated prolonged TTF on mTOR inhibitor-based therapy as compared to prior conventional treatment. Heterogeneity in actionable molecular aberrations was observed, suggesting that multi-assay molecular profiling and individualizing treatment merits investigation.